Czechoslovak economic relations with the developing countries - Dobes, L; Dobes, Leo (1980)
﻿ Work on relations between developing countries (LDCs) and the socialist countries has tended to focus on the Soviet Union because of its superpower status. This thesis adopts an alternative approach by examining relations between LDCs and a smaller, but still important country; because the absence of 'superpower' attitudes and concerns permits a less exclusive identification of the factors involved in bilateral economic relations between LDCs and a planned socialist economy. The immediate post-Stalinist era in Eastern Europe coincided with the post-colonial era in the Third World. Because Western literature in this period often imputed sinister motives to socialist countries 5 efforts to develop relations with the new states, this thesis has analysed (with the benefit of two decades of hindsight) the relative importance of political and economic factors in the evolution of Czechoslovak/LDC economic relations. Qualitative analysis was reinforced where appropriate with statistical correlations between economic variables (including delta coefficients) and an index of UN voting patterns developed to approximate bilateral Czechoslovak/LDC 'political affinity'. The comprehensive approach adopted contributed significantly to placing specific aspects of bilateral relations between Czechoslovakia and a core group of 41 LDCs in a broader and therefore enhanced perspective. A number of selected but interrelated issues were examined - inter alia, historical antecedents; the direction, composition, and stability of trade; payments; politics; the terms of trade; barriers to trade; development assistance; and the arms trade - within the analytical framework of the 'intensity' approach to foreign trade. It was found that trade with LDCs has been historically concentrated on a small number of the larger economies, consisting of an exchange of Czechoslovak manufactures for raw materials or semi-processed products. The overall trade share of LDCs has declined slowly but steadily since the early sixties. Relations in the period 1960-1975 appear to have been based primarily on commercial considerations. World prices are allegedly preferred in trade, entrepots are used, development assistance is extended with domestic interests in mind, etc. Political biases are apparent only on the broader level: e.g. the preponderance of India and Egypt in trade with LDCs.